Intrinsically Magnetic Cells: A Review on Their Natural Occurrence and Synthetic Generation - Pekarsky, Alexander; Spadiut, Oliver (Frontiers in Bioengineering and Biotechnology, 2020)
The magnetization of non-magnetic cells has great potential to aid various processes in medicine, but also in bioprocess engineering. Current approaches to magnetize cells with magnetic nanoparticles require cellular uptake or adsorption through in vitro manipulation of cells. A relatively new field of research is “magnetogenetics” which focuses on in vivo production and accumulation of magnetic material. Natural intrinsically magnetic cells (IMCs) produce intracellular, magnetic nanoparticles and are called magnetotactic bacteria (MTB). In recent years, researchers have unraveled function and structure of numerous proteins from MTB. Furthermore, protein engineering studies on such MTB proteins and other potentially magnetic proteins, like ferritins, highlight that in vivo magnetization of non-magnetic hosts is a thriving field of research. This review summarizes current knowledge on recombinant IMC generation and highlights future steps that can be taken to succeed in transforming non-magnetic cells to IMCs.